Nośność Sprężysta Rurociągu Grubościennego - M. Mrowiec; M. Życzkowski (Engineering Transactions)
The aim of this paper is to determine the limit curves in the plane of which the coordinates are the bending moment and the internal pressure, for the elastic load carrying capacity of a thick- walled pipe-line (the appearance of first plastic strains in a perfect elastic-plastic material). Three typical cases are considered: those of plane stress, plane strain and the case of a cylinder closed by bottoms. These cases are treated collectively by introducing the coefficient y the respective values of which are ? = 0, P = y and p = 0.5. On the basis of the Huber-Mises-Hencky strain theory the upper bound of the equivalent stress 0o is found. It is shown that it can be reached at the inner or the outer radius only, not the middle radius. The limit curves are composed of ellipse arches. Figure 2 shows the relation between the limit curves and the wall thickness and Fig. 3 the dependency of these curves on the character of the work (coefficient ϕ). Figure 4 represents an example of the pattern of the lines of equal equivalent stresses σ0 in a cross-section of the pipe.